2016
DOI: 10.1007/s10029-016-1518-2
|View full text |Cite
|
Sign up to set email alerts
|

Incisional hernias after laparoscopic and robotic right colectomy

Abstract: Purpose Incisional hernia (IH) is a common complication after colectomy, with impacts on both healthcare utilization and quality of life. The true incidence of IH after minimally invasive colectomy is not well described. The purpose of this study was to examine the IH incidence after minimally invasive right colectomies (RC), and to compare the IH rate after laparoscopic (L-RC) and robotic (R-RC) colectomies. Methods This is a retrospective review of patients undergoing minimally invasive RC at a single inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 19 publications
2
22
0
1
Order By: Relevance
“…compared RRH with ICA and LRH with ECA, identifying a significantly higher rate of anastomotic leak ( P < 0.05) following LRH of 8.3% compared with 0% following RRH . Otherwise no other included study reported a difference between groups with a range of 0%–2.9% for RRH and 0%–10% for LRH . Megevand et al .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…compared RRH with ICA and LRH with ECA, identifying a significantly higher rate of anastomotic leak ( P < 0.05) following LRH of 8.3% compared with 0% following RRH . Otherwise no other included study reported a difference between groups with a range of 0%–2.9% for RRH and 0%–10% for LRH . Megevand et al .…”
Section: Resultsmentioning
confidence: 98%
“…The incidence of postoperative ileus was reported in 10 studies with rates of 0%–12.4% and 0%–13% for RRH and LRH, respectively (Table ) . No study reported a significant difference between the robotic and laparoscopic approaches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ileocecal resection requires a small abdominal incision to pull out the specimen and reconstruct the digestive tract, but several complications have been reported, including incisional hernia, wound infection, and adhesion relating to the small abdominal incision. The overall rate of incisional hernia after laparoscopic right colectomy reportedly ranges from 1.5% to 17.4% . Because the specimen is retrieved intraluminally through the anus during LECS, and mini‐laparotomy is unnecessary, the risk of those complications is estimated to be drastically reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The overall rate of incisional hernia after laparoscopic right colectomy reportedly ranges from 1.5% to 17.4%. [7][8][9] Because the specimen is retrieved intraluminally through the anus during LECS, and mini-laparotomy is unnecessary, the risk of those complications is estimated to be drastically reduced.…”
Section: Discussionmentioning
confidence: 99%